Leadership and identity politics on the eve of the Israeli 2015 elections: children's perspectives. Issue 3 (1st October 2016) - Alon-Tirosh, Michal; Hadar-Shoval, Dorit
Abstract: This article addresses identity politics in Israeli society on the eve of the 2015 elections as recounted in interviews with Israeli children. Children belonging to four groups of Israeli society (secular Jews, religious Jews, Ethiopian Jews and Arabs) were asked about the suitability of male and female candidates running for the position of Israeli prime minister. The findings can be viewed through two types of power relations: gender power relations and power relations between groups of different collective identities. Gender power relations reflect gender inequality. One example of this inequality is that female candidates are perceived as transparent in regard to their suitability for the post of prime minister. Power relations between different groups reflect the hierarchy of collective identities; secular Jews hold a hegemonic status, while other groups weaken each other in order to strengthen their own relative status within the hierarchy. This study shows that power relations between the four groups in Israeli society are present and internalized as early as elementary school a finding that holds important implications as Israel works toward its ultimate goal of democracy.